(untitled) (Journal of Face Aesthetics, 2020)
Androgenetic alopecia is a common condition, accounting for about 95% of all male hair loss. Standard therapeutic solutions recommend the use of minoxidil, finasteride, spironolactone, nutritional supplementation, phototherapy and hair transplant surgery. An increasingly popular alternative method that has been used in the case report is platelet rich plasma (PRP) mesotherapy characterized by autologous character, minimal invasiveness and no serious side effects. A series of 3 treatments was performed at 3-week intervals. The effects of using medical photographic documentation after completing a series of treatments.